Social Attention Deficits in Children With Autism Spectrum Disorder: Task Dependence of Objects vs. Faces Observation Bias - Mouga, Susana; Castelhano, João; Café, Cátia; Sousa, Daniela; Duque, Frederico; Oliveira, Guiomar; Castelo-Branco, Miguel (Frontiers in Psychiatry, 2021)
Social attention deficits represent a central impairment of patients suffering from autism spectrum disorder (ASD), but the nature of such deficits remains controversial. We compared visual attention regarding social (faces) vs. non-social stimuli (objects), in an ecological diagnostic context, in 46 children and adolescents divided in two groups: ASD (N=23) and typical neurodevelopment (TD) (N=23), matched for chronological age and intellectual performance. Eye-tracking measures of visual scanning, while exploring and describing scenes from three different tasks from the Autism Diagnostic Observation Schedule (ADOS) were analysed: “Description of a Picture”, “Cartoons” and “Telling a Story from a Book”. Our analyses revealed a three-way interaction between Group, Task and Social vs. Object Stimuli. We found a striking main effect of group and a task dependence of attentional allocation: while the TD attended first and longer to faces, ASD participants became similar to TD when they were asked to look at pictures, while telling a story. Our results suggest that social attention allocation is task dependent, raising the question whether spontaneous attention deficits can be rescued by guiding goal-directed actions.